PUBLIC POLITICAL PARTICIPATION IN ELECTIONS IN BANDAR LAMPUNG - Muhammad, Tubagus; Okta , Restu Viandi (Progressive Law Review, 2021)
One indicator of electoral success is the high level of unapologetic participation of the public. High participation guarantees the legitimacy of government and protection of citizens' suffrage. In the 2019 concurrent elections, the low level of political participation in Bandar Lampung, Lampung Province, was low. Participation is important to be researched considering the success of an election can be seen from the level of community participation. Participation is closely related to legitimacy, the higher the level of voter participation in elections, the more legitimate the government it produces. Government supported by the majority of society naturally will be easier to get support for programs and policies to be implemented. The involvement of the public in the selection of his deputy allows for a process of check and balance between the political officials of the election results and their constituents so that the mandate rope between the two is not immediately severed. One indicator of electoral success then is the high level of public participation in voting. Therefore, this research in terms of political participation is an important aspect in the country involving the public in the implementation and implementation of elections. Because the political participation of the community is an important aspect in the order of the State of democracy.